Radiological significance of the sinonasal anatomical variants in recurrent acute rhinosinusitis patients - Sahu, Niranjan; Mohapatra, Satya Sundar G.; Rath, Siba N.; Padhy, Rabindra N. (International Journal of Research in Medical Sciences, 2017)
Background: Recurrent acute rhinosinusitis (RARS), a low form chronic rhinosinusitis is frequently under evaluated. The significance of sinonasal anatomical variants of osteomeatal complex (OMC) and spheno-ethmoidal (SE) recess regions in patients of RARS is assessed. Methods: Retrospective analysis of coronal sinonasal computed tomography images of 120 RARS patients presented with sinonasal anatomical variants during November 2013 to October 2016 was carried out. Patients with acute and expansile sinonasal lesions are excluded. Results: Sinonasal anatomical variants in the regions of OMC and SE recess are responsible for obstruction of normal mucociliary drainage of corresponding paranasal sinuses in presence of inflammation predisposing to RARS. Anatomical variants of nasal septum were, deviated nasal septum (DNS) in 86 (72%) and septal spur in 58 (48%) patients. Anatomical variants in OMC region were, pneumatized middle turbinate (concha bullosa) in 50 (48%), paradoxical middle turbinate in 38 (28%), giant ethmoid bulla in 35 (32%), agger nasi cell in 29 (38%), Haller cell in 23 (15%), pneumatised uncinate process in 20 (18%), medialized uncinate process in 18 (22%) and septated maxillary sinus in 5 (4%) patients. Anatomical variants in SE recess were superior concha bullosa in 14 (12%) and septal bullosa in 11 (9%) patients. Conclusions: OMC pattern of recurrent rhinosinusitis is often prevalent in patients of RARS due to abundance of anatomical variants in the OMC region. DNS or ethmoid bulla when gets associated with concha bullosa increased the incidence of RARS. Present analysis would help surgeons to evaluate RARS patients for selective endoscopic sinus surgery.